SURTO DE Hylesia nanus Walker .(LEPIDOPTERA, SATURNIIDAE) EM Eucalyptus spp. NO ESTADO DO RIO DE JANEIRO - Berti Filho, Evoneo; Cerignoni, João Angelo; Mendes, Flávio Sérgio (REVISTA DE AGRICULTURA, 2015)
SURTO DE Hylesia nanus Walker .(LEPIDOPTERA, SATURNIIDAE) EM Eucalyptus spp. NO ESTADO DO RIO DE JANEIRO